Coastal escape an alternative approach to urban development - Guerrero, Christian Cley S.; Meonada, Jose Mari (Quezon City College of Architecture, University of the Philippines Diliman, 2019)
This research was undertaken in acknowledgement of the various benefits of coastal resources to urban daily life. Premises indicate that coastal resources imply a variety of design implications in architecture and urban design / planning in order to integrate its benefits to the daily life of urban dwellers. As a response, this research therefore organizes a body of knowledge that summarizes these benefits and their corresponding design implications for the reference of both urban developers in the country and local government planning units - introducing an alternative set of design considerations or "approach" to urban development coined "coastal escape". This paper then demonstrates the guidelines' application to an urban development proposal modelled after existing development projects in the country by the private sector - going over a comprehensive analysis of site contexts, development goals and parameters, including the proposed guidelines, to produce a comprehensive design project.
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Urban development -- Philippines